1998
DOI: 10.1074/jbc.273.27.16771
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Novel Peptidase (IImes) from Mesquite (Prosopis velutina) Pollen

Abstract: Although the mesquite plant (Prosopis velutina) is not as widely distributed as some other allergenic species, its pollen can induce serious pollinosis in areas where it is localized. We previously isolated and characterized a peptidase from mesquite pollen with trypsin-like specificity (peptidase I mes ) (Matheson, N., Schmidt, J., and Travis, J. (1995) Am. J. Respir. Cell Mol. Biol. 12, 441-448). Now we have characterized a second enzyme with specificity for hydrophobic residues (mesquite pollen peptidase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Recent results that E*I* formation coincides with liberation of a new N terminus at P1Ј (32,33) demonstrate that within E*I*, I has been cleaved at the P1-P1Ј bond. These results, coupled with the observation that E*I* dissociates on treatment with hydroxylamine (34), provide strong evidence that the covalent bond within E*I* is between the proteinase active site serine hydroxyl (Ser-195 in ␣-chymotrypsin) and the liberated P1 carboxyl of the serpin and corresponds either to acyl-enzyme or to the tetrahedral intermediate (35) resulting from water attack on the acylenzyme. Indeed, these species may be in mobile equilibrium with each other.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Recent results that E*I* formation coincides with liberation of a new N terminus at P1Ј (32,33) demonstrate that within E*I*, I has been cleaved at the P1-P1Ј bond. These results, coupled with the observation that E*I* dissociates on treatment with hydroxylamine (34), provide strong evidence that the covalent bond within E*I* is between the proteinase active site serine hydroxyl (Ser-195 in ␣-chymotrypsin) and the liberated P1 carboxyl of the serpin and corresponds either to acyl-enzyme or to the tetrahedral intermediate (35) resulting from water attack on the acylenzyme. Indeed, these species may be in mobile equilibrium with each other.…”
mentioning
confidence: 73%
“…Given the evidence that E*I* may correspond to acyl-enzyme or to the final tetrahedral intermediate (35) resulting from water attack on the acyl-enzyme, an interesting possibility is that the observed cleaved I may arise from the breakdown of the final tetrahedral intermediate during quench/analysis.…”
mentioning
confidence: 99%
“…E*I*s formed from a variety of serpin-serine proteinase pairs are stable to both boiling water and SDS treatment, implying covalent bond formation between enzyme and serpin. Parallel studies by both Lawrence et al (15) and Wilcynska et al (16) have clearly shown that the P1-P1Ј bond is cleaved within the complexes formed by several such pairs (including plasminogen activator inhibitor-1:t-plasminogen activator, plasminogen activator inhibitor-1:u-plasminogen activator, ␣ 1 -proteinase inhibitor:human neutrophil elastase, ␣ 1 -proteinase inhibitor: porcine pancreatic elastase and ␣ 2 -antiplasmin:plasmin), providing strong evidence that E*I* corresponds either to an acyl enzyme, or, less likely given the stability of E*I*, to the tetrahedral intermediate formed by water attack on the acyl enzyme (17).…”
mentioning
confidence: 96%
“…Early studies favored trapping of the proteinase at the acyl intermediate stage of proteolysis, based on the observation that the serpin reactive center loop was cleaved in the stable complex with proteinase (8, 16 -18). However, NMR evidence later suggested that stabilization of the serpin-proteinase complex at the acyl intermediate stage occurred only under denaturing conditions and that under native conditions, the complex was stabilized at the tetrahedral intermediate stage (19). Yet more recent findings have questioned the NMR data by showing that, even under nondenaturing conditions, the reactive center loop is cleaved concomitant with formation of the serpin-proteinase complex, thus supporting an arrest of the serpin-proteinase reaction at the acyl intermediate stage (20 -22).…”
mentioning
confidence: 99%